Early life predictors of child development at kindergarten: a structural equation model using a longitudinal cohort - Turner, Sarah E.; Goguen, Stephanie; Dufault, Brenden; Mayer, Teresa; Mandhane, Piushkumar J.; Moraes, Theo J.; Turvey, Stuart E.; Simons, Elinor; Subbarao, Padmaja; Azad, Meghan B. (Frontiers in Public Health, 2025)
IntroductionEarly child development sets the stage for lifelong health. Identifying early life factors related to child development can help guide programs and policies to bolster child health and wellbeing. The objective of this research was to examine how a broad range of predictors, measured prenatally to the third year of life, are related to child development at kindergarten.MethodsWe linked survey data from the Manitoba site of the CHILD Cohort Study with data from the Early Development Instrument (EDI) assessment, completed in kindergarten by the Manitoba public school system (n = 442 children). The EDI measures five domains of development (ex. language, physical), scored to indicate the bottom 10% (i.e., ‘vulnerable’) of the population on one or more domains. Using structural equation modelling, we grouped 23 predictors of child development into six latent factors including prenatal exposures, child health and lifestyle, family stress, and socioeconomic status (SES). We examined the associations between each latent factor and EDI vulnerability.ResultsOverall, 20.1% of children were vulnerable on one or more EDI domains. Higher family stress at 1 year and 3 years was related to a 0.20 (p-value ≤0.001) and 0.33 (p-value ≤0.001) standardized increase of EDI vulnerability. Higher SES was related to a-0.26 (p-value =0.01) standardized decrease of EDI vulnerability, and this link was partially mediated through family stress at 3 years (10.6% mediated). Prenatal exposures (e.g., maternal diet quality), as well as child health and lifestyle factors (e.g., weekday sleep) were not related to EDI vulnerability.ConclusionSupporting parental mental health and programs to reduce early life parenting stress, as well as targeting supports to those living with low SES, appear to be priority areas that could help to improve early child development.